2009
DOI: 10.1016/j.bbabio.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ transfer from the ER to mitochondria: When, how and why

Abstract: The heterogenous subcellular distribution of a wide array of channels, pumps and exchangers allows extracellular stimuli to induce increases in cytoplasmic Ca2+ concentration ([Ca2+]c) with highly defined spatial and temporal patterns, that in turn induce specific cellular responses (e.g. contraction, secretion, proliferation or cell death). In this extreme complexity, the role of mitochondria was considered marginal, till the direct measurement with targeted indicators allowed to appreciate that rapid and lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
317
1
21

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(344 citation statements)
references
References 137 publications
(141 reference statements)
5
317
1
21
Order By: Relevance
“…through L-type Ca 2+ channel and NCX (sodium-calcium exchanger)). 16 Although ryanodine receptors (RyRs) are the major cardiac SR/ER Ca 2+ -release channels involved in excitation-contraction coupling (ECC) 17 and ischemia-reperfusion (IR) injury, 18 recent studies reported an increasing role for inositol 1,4,5-trisphosphate receptors (IP 3 Rs) Ca 2+ -release channels in the modulation of ECC and cell death. 19,20 Ca 2+ -handling proteins of ER and mitochondria are highly concentrated at mitochondria-associated ER membranes (MAMs), providing a direct and proper mitochondrial Ca 2+ signaling, including VDAC, Grp75 and IP 3 R1.…”
mentioning
confidence: 99%
“…through L-type Ca 2+ channel and NCX (sodium-calcium exchanger)). 16 Although ryanodine receptors (RyRs) are the major cardiac SR/ER Ca 2+ -release channels involved in excitation-contraction coupling (ECC) 17 and ischemia-reperfusion (IR) injury, 18 recent studies reported an increasing role for inositol 1,4,5-trisphosphate receptors (IP 3 Rs) Ca 2+ -release channels in the modulation of ECC and cell death. 19,20 Ca 2+ -handling proteins of ER and mitochondria are highly concentrated at mitochondria-associated ER membranes (MAMs), providing a direct and proper mitochondrial Ca 2+ signaling, including VDAC, Grp75 and IP 3 R1.…”
mentioning
confidence: 99%
“…19,20 Mitochondrial [Ca 2 þ ] is commonly regarded as an important determinant in cell sensitivity to apoptotic stimuli. 21 Indeed, mitochondrial Ca 2 þ accumulation acts as a 'priming signal' sensitizing the organelle and promoting the release of caspase cofactors, both in isolated mitochondria as well as in intact cells. 22,23 In this context, ER-mitochondria contacts mediate the tight and efficient Ca 2 þ transmission between the two organelles and thus could represent a potential regulatory site for cell death signals.…”
mentioning
confidence: 99%
“…Mitochondrial architecture is important for crucial mitochondrial functions, including ATP generation via oxidative phosphorylation (OXPHOS), calcium homeostasis and programmed cell death (apoptosis) (Frey and Mannella , 2000 ;Frezza et al , 2006 ;Clapham , 2007 ;Strauss et al , 2008 ;Rizzuto et al , 2009 ;Martins de Brito and Scorrano , 2010 ;Davies et al , 2011 ;Green et al , 2011 ). Accordingly, alterations of mitochondrial morphology are a hallmark of numerous human diseases, ranging from myopathies, neuropathies and neurodegenerative disorders to metabolic diseases and different types of cancer.…”
Section: Implications Of Minos Functions For Human Diseasementioning
confidence: 99%